Rationalization of soccer training in terms of health effects of metropolitan smog and activity on the artificial turf - Duda, Henryk; Rydzik, Łukasz; Soroka, Andrzej; Sokołowski, Kamil (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The aim of the study was to determine the response of football players to physical exertion taking into account the degree of smog-related air pollution. This response was also assessed in a training environment on an artificial football pitch, where the concentration of particulate air pollutants in the area is higher due to the release of dust from rubber granules found on the grass of artificial football pitches. The study was conducted among 20 male recreational football coaches. The mean age of the participants was 22.8±2.3 years. Continuous research from 2019 to 2021 was conducted during programme football training on an artificial football pitch at a sports facility in Kraków. The body’s response (resting and exercise heart rate) was studied in football players under smog and clean air conditions (Samsung AX60R5080WD/EU air pollution meters, Air Visual Pro). The results of the study concluded that the degree of air pollution (smog) influences the body’s response (higher HR value). It has also been observed that artificial turf, due to the abrasion of the granules, is characterised by a higher level of air pollution, which, in addition to containing toxic chemical compounds, has a negative impact on the health of the footballer.